(untitled) (American Journal of IR 4.0 and Beyond, 2024)
In the era of global Information Communication and Technology (ICT) development, governmental services are increasingly being digitized to enhance accessibility and efficiency. This shift towards digitalization, spurred by widespread smartphone and internet use, has fostered a tech-savvy populace. Nepal, in particular, has seen significant progress in its communication sector with a growing number of telephone and internet users. This study examines Nepal’s digitalization status and implementation challenges and proposes strategies and policies to address these challenges. Employing analytical and descriptive research methodologies, the study utilizes both qualitative and quantitative data from secondary sources like published research articles, books, interviews, and surveys. Convenience sampling is used, and statistical techniques including descriptive statistics, correlation, and regression analyses are applied. Key findings indicate moderate levels of perceived information quality, system quality, service quality, usage intentions, user satisfaction, and net system benefits. Correlation analysis shows strong positive relationships between these variables, while regression analysis reveals their significant impact on net system benefits. Qualitative data highlights government initiatives, impacts on citizens, and challenges like employee resistance and usability issues. The study emphasizes the need for centralized data retrieval using the National ID system to streamline processes, offering valuable insights for enhancing digitalization in Nepal.